The CRASH report: emergency management dilemmas facing acute physicians in patients with pulmonary arterial hypertension. Issue 11 (12th September 2017) - Price, Laura C; Dimopoulos, Konstantinos; Marino, Philip; Alonso-Gonzalez, Rafael; McCabe, Colm; Kemnpy, Aleksander; Swan, Lorna; Boutsikou, Maria; Al Zahrani, Ahmed; Coghlan, Gerry J; Schreiber, Benjamin E; Howard, Luke S; et al.
Abstract : Treatment of acute emergencies in patients with pulmonary arterial hypertension (PAH) can be challenging. In the UK and Ireland, management of adult patients with PAH is centred in eight nationally designated pulmonary hypertension (PH) centres. However, many patients live far from these centres and physicians in local hospitals are often required to manage PAH emergencies. A committee of physicians from nationally designated PH centres identified the 'most common' emergency clinical scenarios encountered in patients with PAH. Thereafter, a review of the literature was performed centred on these specified topics and a management approach was developed based on best available evidence and expert consensus. Management protocols were developed on the following PAH emergencies: chest pain (including myocardial ischaemia), right ventricular failure, arrhythmias, sepsis, haemoptysis ('CRASH'), as well as considerations relevant to surgery, anaesthesia and pregnancy. Emergencies are not uncommon in PAH. While expertise in PAH management is essential, all physicians involved in acute care should be aware of the principles of acute management of PAH emergencies. A multidisciplinary approach is necessary, with physicians from tertiary PH centres supporting care locally and planning safe transfer of patients to PH centres when appropriate.